2019
DOI: 10.4081/oncol.2019.409
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive overview of mitochondrial DNA 4977-bp deletion in cancer studies

Abstract: Mitochondria are cellular machines essential for energy production. The biogenesis of mitochondria is a highly complex and it depends on the coordination of the nuclear and mitochondrial genome. Mitochondrial DNA (mtDNA) mutations and deletions are suspected to be associated with carcinogenesis. The most described mtDNA deletion in various human cancers is called the 4977-bp common deletion (mDNA4977) and it has been explored since two decades. In spite of that, its implication in carcinogenesis still unknown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 118 publications
(146 reference statements)
2
26
0
Order By: Relevance
“…The mtDNA 4977 deletion has been considered as a pathogenic mutation in human as the loss of the tRNA genes and coding regions could cause a failure of ATP production and mitochondrial dysfunctions. Increased OS has been reported to trigger the accumulation of deletions in mtDNA [21,22]. Consistent with evidence linking OS with mitochondrial destruction [7,23], our study found that mtDNA 4977 DR was a risk factor for PCOS independent of metabolic parameters.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The mtDNA 4977 deletion has been considered as a pathogenic mutation in human as the loss of the tRNA genes and coding regions could cause a failure of ATP production and mitochondrial dysfunctions. Increased OS has been reported to trigger the accumulation of deletions in mtDNA [21,22]. Consistent with evidence linking OS with mitochondrial destruction [7,23], our study found that mtDNA 4977 DR was a risk factor for PCOS independent of metabolic parameters.…”
Section: Discussionsupporting
confidence: 90%
“…The mtDNA 4977 deletion, involving huge destruction of almost one-third of the length of mtDNA, is the most common large deletion in the mitochondrial genome [21]. The deleted region contains 5 tRNA genes and 7 genes encoding 4 complex I subunits, 1 complex IV subunit, and 2 complex V subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mtDNA 4977 was discovered to vary between 0% and 100% in a variety of human cancers. 20 …”
Section: Discussionmentioning
confidence: 99%
“…mtDNA 4977 eliminates all five tRNA genes (tRNA Gly , tRNA Arg , tRNA His , tRNA Ser , and tRNA Leu ) and seven genes encoding four Complex I subunits (ND3, ND4, ND4L, partial ND5), one Complex IV subunit (COX III), and two Complex V subunits (ATP6 and partial ATP8), that are vital for sustaining a normal mitochondrial OXPHOS function. 20 …”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial DNA (mtDNA) is a circular molecule of 16569 bp, coding for two 2 ribosomal RNAs (12S and 16S), 22 transfer RNAs and 13 essential protein subunits of the oxidative phosphorylation system (OXPHOS) [14]. It is well known that (mtDNA) has a mutation rate several times higher than nuclear DNA [15], due to its limited repair mechanisms, lack of protective histones and its close proximity to the electron transport chain, which continuously generates free radicals [16]; in addition, mtDNA is organized in an economic pattern with its genes lacking introns [17]. It was in 1956, when Otto Warburg observed that cancers ferment glucose in the presence of oxygen, proposing that abnormalities in mitochondrial respiration may be responsible for cancer production [16, 18, and 19].…”
Section: Introductionmentioning
confidence: 99%